The Evolution of Digital Public Relations Ethics under Arab Media Legislation (The International Journal of Educational Sciences and Arts, 2026)
The Arab world is witnessing a rapid digital transformation that has led to significant developments in the field of digital public relations. Digital platforms and social media have become essential tools for building a public image and managing relationships with the public. This development has also given rise to complex ethical challenges related to transparency, credibility, privacy protection, and the spread of misinformation, necessitating the intervention of media legislation to regulate and control these practices.The study's central problem lies in the clear gap between the rapid technological development of digital public relations and the lack of a corresponding development in media legislation. This gap negatively impacts the level of ethical commitment among practitioners and leads to the emergence of unregulated practices. Therefore, this study aims to analyze the relationship between Arab media legislation and the ethics of digital public relations, and to determine the extent to which these laws contribute to promoting responsible professional conduct. The study adopted a descriptive-analytical approach, analyzing media legislation in several Arab countries, including Saudi Arabia, Egypt, the UAE, and Bahrain. It also reviewed previous studies and analyzed professional practices in the digital environment. Furthermore, it drew upon several theories, most notably social responsibility theory, professional ethics theory, and media governance theory, to explain the relationship between legislation and ethical conduct.The study's findings revealed a significant development in digital media legislation across Arab countries. However, this development is uneven and suffers from varying levels of clarity and implementation. The results also highlighted a gap between legal texts and practical application within institutions, stemming from inadequate training and the absence of clear internal policies. The study emphasized that stricter and clearer legislation contributes to higher ethical standards, while its absence or ambiguity leads to increased professional violations.The study also highlighted several contemporary ethical challenges, most notably the lack of transparency in digital content, particularly in advertising and influencer marketing, the spread of misinformation, and privacy issues related to data collection and use. Additionally, it addressed the new challenges arising from the use of artificial intelligence in content production and audience influence. The study concluded with a set of recommendations, most notably the need to unify the Arab legislative framework for regulating digital media, update laws to encompass modern technological developments such as artificial intelligence, and impose clear controls on the disclosure of paid content. It also recommended strengthening professional ethics within institutions by developing clear codes of conduct, training practitioners on legal and ethical aspects, and establishing specialized units for content review and verification.The study concludes that achieving successful professional practice in digital public relations requires the integration of effective media legislation and ethical commitment, as neither can achieve its objectives without the other. This represents the foundation for building a more credible and sustainable digital communication environment in the Arab world.
Keywords: Digital Public Relations; Media Ethics; Media Legislation